Actuality of development of the ambulatory assistance system at the second level by application of mechanisms of the state-private partnership - Kravchenko, V. V. (Journal of Education, Health and Sport, 2018)
The aim of the research: to determine and substantiate the relevance of the development of the outpatient care system at the secondary level through the use of public-private partnership mechanisms. Materials and methods Research performed using the method of the system approach and analysis, synthesis and generalization, the interpretation of scientific data, as well as the structural-functional approach. Information Base for its implementation have become scientific papers of experts health care organization and management, normative documents, as well as the results of their research. Results of the study In article research and actuality application of the mechanisms of public-private partnership (PPP) in the development of the system of outpatient care at the secondary level, on the basis of consultative diagnostic centers (KDC). Set out the methodological approaches to the formation of KDC on the PPP, which contribute to the development of business processes, mechanisms of mixed economy, attracting the resources of a private investor, the efficiency of the system of municipal KDC. Conclusions The results of the research in the future will be used when designing functional-organizational model of KDC on the principles of public-private partnerships.